2013
DOI: 10.1089/fpd.2012.1356
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure ofStaphylococcus aureusIsolated from Bulk Tank Goat's Milk

Abstract: The presence of Staphylococcus aureus in raw milk can represent a potential threat to human health, due to the introduction of pathogenic strains into dairy food supply chain. The present study was performed to investigate the genetic variation among S. aureus strains isolated from bulk tank goat's milk. The virulence profiles were also assessed to link the isolates with the potential source of milk contamination. A population study was performed on 60 strains using distance-based methods such as pulsed-field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 29 publications
(30 reference statements)
4
9
1
1
Order By: Relevance
“…In contrast, a higher contamination rate of S. aureus was found in raw goat milk, tank milk, and workers' samples than that in other processing sites. This was confirmed in previous reports (Bianchi et al, 2014;Intrakamhaeng, Komutarin Schlegelova et al, 2010;Spanu et al, 2013). Our results indicated that S. aureus was common in different goat milk powder processing plants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, a higher contamination rate of S. aureus was found in raw goat milk, tank milk, and workers' samples than that in other processing sites. This was confirmed in previous reports (Bianchi et al, 2014;Intrakamhaeng, Komutarin Schlegelova et al, 2010;Spanu et al, 2013). Our results indicated that S. aureus was common in different goat milk powder processing plants.…”
Section: Discussionsupporting
confidence: 93%
“…Their potential introduction into the dairy supply chain may represent a serious threat to human health. The tst and sec genes of S. aureus from goat and ovine milk are usually detected together (Lyra et al, 2013;Rosengren, Fabricius, Guss, Sylven, & Lindqvist, 2010;Spanu et al, 2013), which was in agreement with our study, suggesting that these genes may exist together. Pvl is associated with human infections (Chen, Hiramatsu, Huang, Wang, & Lauderdale, 2009) and goat mastitis (Unal et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unsurprisingly the most prevalent species was Staphylococcus aureus (20.14% in sheep and 44.44% in goat) whose presence in sheep and goat milk has been widely demonstrated in Italy: Cortimiglia et al (2015) evidenced in bulk tank sheep’s milk a Staphylococcus aureus prevalence of 43%, Spanu et al (2013) in bulk tank goat’s milk showed a prevalence of 76%. On the other hand, the predominant bacterial genera isolated from cow samples was Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, MRSA have been sporadically identified in bovine milk (Antoci, Pinzone, Nunnari, Stefani, & Cacopardo, 2013;Normanno et al, 2007;Pilla et al, 2012), while they have never been detected in surveys conducted on ovine, caprine or bubaline milk (Cremonesi et al, 2013;Morandi, Brasca, Andrighetto, Lombardi, & Lodi, 2010;Perillo et al, 2012;Spanu et al, 2013;Virdis et al, 2010). At a global level, only a few data are available on the presence of MRSA in dairy products.…”
Section: Phenotypic and Genomic Characterisation Of Methicillin Resismentioning
confidence: 99%